TRANSFORMASI MOTIVASI BELAJAR BAHASA ARAB MENUJU KECINTAAN AL-QUR'AN - Irpan Ilmi (Study Program of Arabic Language Education (PBA), 2026)
The main problem in Arabic language learning at STITNU Al Farabi Pangandaran is the high level of language anxiety and low literacy among students who graduated from general high schools and view this subject as a rigid academic burden. This situation is exacerbated by feelings of religious inferiority and interference from local dialects, which hinder students’ phonetic articulation. This study aims to analyze the transformation of learning motivation through the implementation of the “Linguistic-Qur’anic Model” based on the science of Ashwat. Using a qualitative case study method, data were collected through digital surveys, participatory observation, and analysis of midterm exam results. The findings indicate that focusing on phonetic-spiritual aspects successfully shifted motivation from instrumental to spiritual-transcendental in a significant way. Academic achievements demonstrate that 87% of students achieved accurate makhraj, which led to a reduction in language anxiety and an increase in self-confidence in recitation. The novelty of this study lies in the integration of three stages: sound sensitization, internalization of meaning, and actualization of worship. This model demonstrates that Arabic language instruction grounded in the Qur’an can restore students’ spiritual identity while ensuring the sustainability of their motivation to learn through the refinement of the quality of their daily worship. Keywords: Motivation, Arabic, Qur’an, STITNU Al Farabi, Science of Sounds